Programming 16-bit PIC microcontrollers in C : learning to fly the PIC 24 - Di Jasio, Lucio (Newnes, 2012)
"Expert assembly programmers: Learn how to write embedded control applications in C; Expert 8-bit programmers: Learn how to boost your applications with a powerful 16-bit architecture; Explore the world of embedded control experimenting with analog and digital peripherals, graphic, displays, video and sound"--Cover.